2017
DOI: 10.3382/ps/pew229
|View full text |Cite
|
Sign up to set email alerts
|

ALV-J strain SCAU-HN06 induces innate immune responses in chicken primary monocyte-derived macrophages

Abstract: Avian leucosis virus subgroup J (ALV-J) can cause lifelong infection and can escape from the host immune defenses in chickens. Since macrophages act as the important defense line against invading pathogens in host innate immunity, we investigated the function and innate immune responses of chicken primary monocyte-derived macrophages (MDM) after ALV-J infection in this study. Our results indicated that ALV-J was stably maintained in MDM cells but that the viral growth rate was significantly lower than that in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 54 publications
0
26
0
Order By: Relevance
“…As type I IFNs, IFN-α firstly binds with specific transmembrane receptors and exhibits antiviral activity by stimulating various downstream ISG expression (Schneider et al 2014). At an early stage of viral infection in chicken, a number of ISGs, including the Mx1 and ISG12, were induced (Feng et al 2017) to inhibit virus release or protein lysis, thus enhancing innate immune signaling and antiviral functions . As one of the first depicted inhibitors of virus invasion, the Mx1 gene product broadly inhibits genome replication at an early post-entry step of the virus life cycle (Schneider et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…As type I IFNs, IFN-α firstly binds with specific transmembrane receptors and exhibits antiviral activity by stimulating various downstream ISG expression (Schneider et al 2014). At an early stage of viral infection in chicken, a number of ISGs, including the Mx1 and ISG12, were induced (Feng et al 2017) to inhibit virus release or protein lysis, thus enhancing innate immune signaling and antiviral functions . As one of the first depicted inhibitors of virus invasion, the Mx1 gene product broadly inhibits genome replication at an early post-entry step of the virus life cycle (Schneider et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we determined that chicken primary monocyte-derived macrophages (MDM) were susceptible to ALV-J (40). ALV-J strain SCAU-HN06 (41) rapidly increased the expression of Mx, ISG12-1 , IL-1β, IL-6, and IFN-β in MDM at early infection stages, but Mx, ISG12-1 , and IL-10 expression decreased sharply at 36 h postinfection (40).…”
Section: Immunity Against Alvmentioning
confidence: 99%
“…ALV-J strain SCAU-HN06 (41) rapidly increased the expression of Mx, ISG12-1 , IL-1β, IL-6, and IFN-β in MDM at early infection stages, but Mx, ISG12-1 , and IL-10 expression decreased sharply at 36 h postinfection (40). This result indicated that ALV-J most likely escaped the innate immune response in chicken macrophages.…”
Section: Immunity Against Alvmentioning
confidence: 99%
See 1 more Smart Citation
“…ALV subgroup J (ALV-J) infections greatly enhance the probability of a secondary infection through virally-induced immunosuppression. Our previous studies demonstrated that ALV-J induces host innate immune responses in chicken’s primary monocyte-derived macrophages suggesting that macrophages are important in ALV-J associated immune defense and escape [ 4 ]. ALV-J infection also inhibits differentiation and maturation of chicken bone marrow-derived dendritic cells (BM-DC) and triggers their apoptosis [ 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%